(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Uzbekistan, a country, in Central Asia known for its heritage boasts a society that is diverse and multilingual. The population encompasses individuals who speak languages and dialects such as Uzbek, Russian and different regional languages. As a result the practice of code switching and multilingualism plays a role in communication and social interactions. This linguistic scenario creates a environment that provides valuable insights into the intricate interplay between language usage and identity, within a multilingual setting.